Performance of Quails Given Ration Containing Dragon Fruit Skin Fermented Neurospora crassa - Pane, Doharni; Pakpahan, Rahmaini (Jurnal Online Pertanian Tropik, 2019)
Quail is one type of poultry that must be developed because it has the potential to produce animal protein needs for humans, namely meat and eggs. Because the meat and quail eggs are in great demand by the community, their maintenance is almost evenly distributed throughout Indonesia. Privileges of quails include fast production, do not require large capital, easy maintenance, and do not require large tracts of land. The aimed of this experiment was to determine the effect of providing dragon fruit skin-fermented (DFSF) with fungi Neurospora crassa as an alternative feed material to the performance of quails. The research method are experiments using completely randomized design (CRD), with 5 treatments and 4 replications. if there is a real or very real difference that will be followed by Duncan’s distance test. The treatments given are: A = without giving DFSF, B = giving 4% DFSF, C = giving 8% DFSF, D = giving 12% DFSF and E = giving 16% DFSF. The results showed that differences in the level of DFSF in quail ration gave no significant effect on feed intake, body weight gain and feed conversion of quail ration. It can be concluded that the administration of DFSF up to the level of 16% in the ration can be used as alternative feed ingredients without affecting feed intake, body weight gain and quail feed conversion.